Risk observation in the handling of patients in health professionals of a hospital unit - Fernandes, Carla Sílvia Neves da Nova (2018)
Background & Aim: There is a high incidence of work-related musculoskeletal injuries in health professionals, namely nurses and nursing assistants, especially associated with the handling and transfer of dependent patients. The present study intends to evaluate the risks of injuries of the health professionals through the observation of the handling of dependent patients. Materials & Methods: A descriptive and correlational study was performed using the observation of the care provided by nurses and nursing assistants. This study was developed in a hospital of the City of Gondomar-Portugal, data collection was carried out between January and March 2018. 149 Professionals were selected by convenience. The data collected were analysed using IBM SPSS® Statistics version 24.0. Results: The sample consisted of 149 participants, mostly female. Concerning the assessment of the burden associated with the handling of dependent patients, it was considered excessive by 74.5% of the professionals. Regarding the application of the Graça Risk Assessment Scale (2008), only 7% of the activities were considered low risk. Risk behaviours associated with inadequate space during the procedure, equipment not properly positioned, almost non-use of mobility aids, and failure to use the patient's collaboration to reduce the effort associated with the procedure were observed. Conclusion: The knowledge obtained through this study will allow the implementation of strategies to reduce the likelihood of pain and musculoskeletal injury related to work.